2022
DOI: 10.1002/smll.202201753
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and Confinement in Ultrathin Chalcogenide Films as Exemplified by GeTe

Abstract: Chalcogenides such as GeTe, PbTe, Sb2Te3, and Bi2Se3 are characterized by an unconventional combination of properties enabling a plethora of applications ranging from thermo‐electrics to phase change materials, topological insulators, and photonic switches. Chalcogenides possess pronounced optical absorption, relatively low effective masses, reasonably high electron mobilities, soft bonds, large bond polarizabilities, and low thermal conductivities. These remarkable characteristics are linked to an unconventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
1
14
1
Order By: Relevance
“…[81] Our suggestion for such use is to grow high-quality thin films to minimize the presence of inverse blocks, allowing tuning of optical properties more effectively. The bonding mechanism and optical characters in layered chalcogenides could be further explored by evaluating the thickness-dependent properties in ultrathin films [82][83][84][85][86] or in the alternately grown heterostructure thin films, such as the TiTe 2 /Sb 2 Te 3 heterostructure. [87][88][89][90] At last, we note that presence of the inverse block defects should also affect the electronic and thermal conduction like other extended defects, such as swapped bilayers [91] and stacking faults with non-QL blocks, [92] which could be tailored for thermoelectric [93,94] and topological [92,95] applications of trigonal Sb 2 Te 3 and related chalcogenides.…”
Section: Discussionmentioning
confidence: 99%
“…[81] Our suggestion for such use is to grow high-quality thin films to minimize the presence of inverse blocks, allowing tuning of optical properties more effectively. The bonding mechanism and optical characters in layered chalcogenides could be further explored by evaluating the thickness-dependent properties in ultrathin films [82][83][84][85][86] or in the alternately grown heterostructure thin films, such as the TiTe 2 /Sb 2 Te 3 heterostructure. [87][88][89][90] At last, we note that presence of the inverse block defects should also affect the electronic and thermal conduction like other extended defects, such as swapped bilayers [91] and stacking faults with non-QL blocks, [92] which could be tailored for thermoelectric [93,94] and topological [92,95] applications of trigonal Sb 2 Te 3 and related chalcogenides.…”
Section: Discussionmentioning
confidence: 99%
“…A similar to the data processing in previous studies. [9] The contributions of ellipsometry spectra and reflectance spectra to the fitted dielectric function were weighted by a factor to make them contribute equally to the mean squared deviation. A Downhill simplex method was employed for the unconstrained optimization.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, an unusual thickness‐dependence of film properties has already been reported for the monochalcogenide Germanium Telluride (GeTe). [ 9 ] Such monochalcogenides are characterized by a number of unconventional properties, too. They possess a moderate electrical conductivity (σ ≈ 10 2 − 10 4 S cm −1 ), a large optical dielectric constant (ε ∞ > 15), large Born effective charges ( Z * ≈ 5 − 8) and large Grüneisen parameters (γ > 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The destruction of the longer bonds is induced by photoexciting electrons from highenergy states in the valence band to low-energy states in the conduction band, enhancing the concentration of nonequilibrium charge carriers. These charge carriers populate antibonding states of the weaker metavalent bonds, 34 as shown in the COHP curves in Figure S6, leading to structural relaxation and bond rupture, causing the collapse of the long-range order. This mechanism effectively opens a path for lowering the energy barrier for bond breaking and triggering structural disorder at a temperature lower than the nominal melting point, similar to photoexcitation preferential bond rupture in As 2 S 3 35 and GST.…”
mentioning
confidence: 99%